2015
DOI: 10.4103/2249-4863.161345
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual characteristics and prevalence of dysmenorrhea in college going girls

Abstract: Background:Dysmenorrhea is a common gynecological condition with painful menstrual cramps of uterine origin. Prevalence of primary dysmenorrhea is not yet clearly studied in central India.Objective:To study prevalence of primary dysmenorrhea in young girls and to evaluate associated clinical markers of dysmenorrhea.Materials and Methods:In a cross-sectional study, data was collected among 310 girls (18–25 years) on age at menarche, presence and absence of dysmenorrhea, dysmenorrhea duration, pre-menstrual symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 17 publications
7
28
1
9
Order By: Relevance
“…According to the present study, there was no significant association between menarche age and dysmenorrhea, which was in accordance with a study by Kural et al (1). However, Shrotriya revealed a significant correlation between these variables, which could be due to the longer exposure of prostaglandins, leading to a higher incidence of uterine dysmenorrhea in adolescents with early menarche (8).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…According to the present study, there was no significant association between menarche age and dysmenorrhea, which was in accordance with a study by Kural et al (1). However, Shrotriya revealed a significant correlation between these variables, which could be due to the longer exposure of prostaglandins, leading to a higher incidence of uterine dysmenorrhea in adolescents with early menarche (8).…”
Section: Discussionsupporting
confidence: 81%
“…Primary dysmenorrhea is a common gynecological condition, characterized by contractions due to prostaglandin release in the secretory phase (1). Its prevalence varies from 51% to 92.5%, based on the results of previous studies on female adolescents (2).…”
Section: Introductionmentioning
confidence: 99%
“…2017; 19(3):e40856. 51,52). Moreover, the prevalence of severe dysmenorrhea was 16%, which was comparable to the 12% -14% that was reported in the community-based studies in the World Health Organization review (3) and 5%-20% that was reported in another review in developing countries (48).…”
Section: Discussionsupporting
confidence: 69%
“…The estimated prevalence of dysmenorrhea varies from 20% to 95% in various studies. 4 Irregular cycles reported in this study is 44.65% which is much higher when compared to other Indian studies. Sheetu et al, reported 24.3% of adolescent girls suffer from irregular cycles.…”
Section: Discussioncontrasting
confidence: 59%